2021
DOI: 10.1186/s11689-021-09382-1
|View full text |Cite|
|
Sign up to set email alerts
|

The prevalence and profile of autism in individuals born preterm: a systematic review and meta-analysis

Abstract: Introduction Preterm birth (<37 weeks) adversely affects development in behavioural, cognitive and mental health domains. Heightened rates of autism are identified in preterm populations, indicating that prematurity may confer an increased likelihood of adverse neurodevelopmental outcomes. The present meta-analysis aims to synthesise existing literature and calculate pooled prevalence estimates for rates of autism characteristics in preterm populations. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 83 publications
1
24
0
Order By: Relevance
“…Poor social communication skills and restricted patterns of repetitive behavior known as autism spectrum disorders (ASD) are other adverse neurodevelopmental outcomes that may develop in preterm infants. Preterm infants have a 3.3 times higher chance of autism diagnosis than full-term infants [ 56 ]. Clinical studies have shown an imbalanced gut microbial composition and metabolites in preterm infants with ASD.…”
Section: Common Gut-microbiota-associated Complications In Preterm In...mentioning
confidence: 99%
“…Poor social communication skills and restricted patterns of repetitive behavior known as autism spectrum disorders (ASD) are other adverse neurodevelopmental outcomes that may develop in preterm infants. Preterm infants have a 3.3 times higher chance of autism diagnosis than full-term infants [ 56 ]. Clinical studies have shown an imbalanced gut microbial composition and metabolites in preterm infants with ASD.…”
Section: Common Gut-microbiota-associated Complications In Preterm In...mentioning
confidence: 99%
“…TIARA is a collaboration between KU Leuven, Ghent University, and societal partners, that is conducted in Flanders, Belgium (www.tiara-onderzoek.be). Children participating in TIARA belong to one of two groups, each with an elevated likelihood of developing autism, namely (a) infant siblings of children with an established autism diagnosis (Messinger et al, 2015;Ozonoff et al, 2011), (b) infants born prematurely, at a gestational age of less than 30 weeks (Agrawal et al, 2018;Laverty et al, 2021, Vermeirsch et al, 2021. Siblings were recruited through centres for developmental disorders, rehabilitation centres, well-baby clinics, home guidance centres, centres for child and adolescent psychiatry, and paediatricians in Flanders, Belgium.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Given the heritability of autism, siblings have a 7-19.5% chance of developing autism themselves (Messinger et al, 2015;Szatmari et al, 2016), compared to a 0.62-1.7% chance in the general population (Elsabbagh et al, 2012;Maenner et al, 2021). More recently, a second group of prematurely born infants (i.e., infants born at a gestational age of less than 32 weeks; 'pre-terms'), has been identified as being at EL of autism, having a chance of 7-13% to develop autism (Agrawal et al, 2018;Laverty et al, 2021;Vermeirsch et al, 2021). Their EL is thought to be the result of interactions between a biological vulnerability and exposure to environmental stressors that would initiate a foetal immune response, leading to both pre-term birth and altered neurodevelopment (Erdei & Dammann, 2014;Limperopoulos, 2009).…”
mentioning
confidence: 99%
“…Given that the socio‐communicative features of ASD usually become visible after the child's first birthday (Szatmari et al, 2016), prospective neuroimaging studies of infants at elevated‐likelihood (EL) for ASD might be able to identify early postnatal changes in the brain that occur before apparent behavioral atypicalities, and thus bridge the gap between early neural development and later ASD characteristics. Accumulated evidence has indicated that infants with genetic or environmental vulnerabilities are more susceptible to ASD than other infants, such as having an older sibling with ASD (Messinger et al, 2015; Ozonoff et al, 2011), and premature delivery (Agrawal et al, 2018; Laverty et al, 2021; Verhaeghe et al, 2016).…”
Section: Introductionmentioning
confidence: 99%